The link between glucometabolic status and nesfatinemia in hypertensive obese patients - Візір, М.О.; Ковальова, Ольга Миколаївна; Vizir, M.; Kovalyova, Olga (Національна академія медичних наук України, 2019)
The link between glucometabolic status and nesfatinemia in hypertensive obese patients
Keywords: glucometabolic status; nesfatinemia; hypertensive obese patients; risk factors of cardiovascular diseases